Optimizing STEM-Based Interactive Flipbooks to Strengthen Students' Science Literacy - Ummi Hanik; Saminan; Ibnu Khaldun (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and assess the effectiveness of STEM-based interactive flipbook media in enhancing senior high school students' science literacy. Science literacy encompasses conceptual understanding, critical thinking, information evaluation, and evidence-based decision-making. The research employed a Research and Development (R&D) design with the ADDIE model encompassing analysis, design, development, implementation, and evaluation stages. Participants included 64 grade X students divided into experimental and control groups. Instruments included science literacy tests, observation sheets, and questionnaires. The findings indicated a notable increase in the experimental group's N-Gain score (0.68) compared to the control group (0.31), with t-test results confirming significant differences (p < 0.05). Students reported that the flipbooks were engaging and motivating. These findings support the integration of STEM-based interactive media as innovative alternatives in digital science classrooms. This work contributes a novel approach by integrating STEM design into digital flipbooks specifically for green chemistry instruction, which remains underexplored in current science education.